Avaliação do programa de residência integrada em saúde - ênfase cardiopneumologia: estratégia de educação permanente dos/as trabalhadores/as do SUS, no Hospital de Messejana, em Fortaleza - CE - Peixoto, Juliana Araújo (2021)
The research evaluated the Integrated Health Residency Program (RIS) of the School of Public Health of Ceará (RIS / ESP-CE), Multiprofessional highlight in Cardiopneumology, in view of the permanent education of workers at the Hospital de Messejana Dr. Carlos Alberto Studart Gomes. As a way of working the phenomena found in the research, a protocol for the use of an investigative proposal that goes beyond the emphasis on measuring efficiency, efficacy and effectiveness in the field of evaluation of public policies. It is the perspective of In-Depth Assessment, which involves four dimensions for the assessment of public policies, they are: an analysis of the institutional content of the program, analysis of the context in which the policy / program was formulated, the institutional path of the policy / program and the temporal and territorial spectrum. The four axes assist in the use and construction of sociocultural indicators in the research, articulated with the scope of thinking and evaluating a public policy on improvements, cultural policies, among others. The work continued to be raised by large issues and reflected in the course of the research, along with theoretical references related to the studies of analytical categories in the field of Public Policy, Public Policy Assessment, State, Social Security with a focus on Public Health Policy, the Unified System Health (SUS), National Policy on Continuing Health Education (PNEPS) and Residency Programs in the Professional Area of Health.